(untitled) (Ustozlar uchun, 2025)
This thesis discusses the importance of language games in teaching English as a Foreign Language (EFL). It highlights how games motivate students, make learning enjoyable, and improve communication skills. The paper analyzes different types of language games—such as vocabulary, grammar, and speaking games—and their impact on students’ linguistic competence. It also explores how games foster cooperation, creativity, and confidence among learners, making the learning process more effective and engaging.